Conservative Agriculture Based on Irrigation Increased the Connections in Inter-Kingdom Co-Occurrence Networks in Arid Zones of Argentina - Frene, Juan Pablo; Faggioli, Valeria Soledad; Covelli, Julieta Mariana; Reyna, Dalila; Sobrero, Patricio; Gabbarini, Luciano; Ferrari, Alejandro; Wall, Luis Gabriel (Wiley, 2025)
Background: Water is one of the most important natural resources in agricultural systems, and the adoption of irrigation systems is producing the expansion of the productive agriculture frontier in Northern Patagonia's arid zone (Argentina). It is critical to evaluate how agricultural management shapes this soil process, like soil microbial communities, nutrient transformation, and ecosystem functions. Aims: For this reason, we analyzed how converting from a semi-arid steppe to an irrigated agricultural system based on no-till and crop rotations impacted the soil microbiome (bacteria and fungi), focusing on the soil core microbiome and the connections between the soil members. Methods: Soil microbiota was analyzed by soil DNA amplicon sequences V3-V4 region of 16S rRNA for bacteria and ITS1–5F region of the ITS rRNA for fungi. Soil enzymes, aggregation, and chemical properties were analyzed related to microbiota structure. Results: Our results suggest that irrigated agriculture enhanced the connections between members but not the number of network members per se. Additionally, we were able to identify a soil core microbiome, which played an important role in the co-occurrence networks. Conclusions: We concluded by demonstrating the critical role that the core microbiome plays in preserving soil bacterial–fungal interactions and their influence on inter-kingdom relationships in complex microbial soil ecosystems in the arid zones of northern Patagonia.